Canada considers a basic income guarantee: can it achieve health for all?. (10th July 2018) - Raphael, Dennis; Bryant, Toba; Mendly-Zambo, Zsofia
Summary: There is little doubt that the implementation of a Basic Income Guarantee (BIG) in Canada and other liberal welfare states would alleviate some of the most egregious examples of absolute poverty that contribute to poor health such as lack of adequate food and shelter and inability to meet basic household and personal needs. BIG would likely improve the health of the most disadvantaged by moving them closer to the relative poverty line. Yet, advocacy for and implementation of BIG carries potential dangers. Since health improves with every step up the income ladder, simply moving people closer to the relative poverty line without providing additional universal benefits and supports common to most other developed nations would limit its health promotion potential. In addition, governing authorities in liberal political economies can use BIG to justify continuing imbalances in economic and political power that skews the distribution of the social determinants of health. In addition, implementation of BIG -- despite its more progressive advocates calls for maintaining or enhancing of existing social programs – can serve as justification for reducing or removing these programs, thereby threatening health.